Pediatric drug development concepts and applications - Mulberg, Andrew E.; Murphy, M. Dianne; Dunne, Julia, 1954-; Mathis, Lisa L. (Chichester, West Sussex, UK : Wiley Blackwell, 2013)
Pediatric Drug Development, Second Edition, encompasses the new regulatory initiatives across EU, US and ROW designed to encourage improved access to safe and effective medicines for children. It includes new developments in biomarkers and surrogate endpoints, developmental pharmacology and other novel aspects of pediatric drug development.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Pediatric pharmacology; Drug development; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Drug development; Pediatric pharmacology; Child; Drug evaluation -- Methods; Age Factors; Clinical Trials as Topic -- standards; Drug Evaluation -- ethics; Drug Evaluation -- standards; Electronic books